ChemInform Abstract: Synthesis of Lipid‐Based Unsymmetrical O, O‐Dialkylphosphites. Issue 35 (September 2015) - Berchel, Mathieu; Haddad, Jimmy; Le Corre, Stephanie S.; Haelters, Jean‐Pierre; Jaffres, Paul‐Alain
Abstract The title reaction implies the use of H‐phosphonate monoester ammonium salts (I) which are coupled with fatty alcohols (II) in the presence of pivaloyl chloride as coupling reagent.